Internal and External Factors Affecting The Size of Paddy Field Sold - Endang Rostiana; Yusup Fatah Hillah (Muhammadiyah University Press, 2016)
This study attempted to identify internal condition of the farmers who sold their paddy field and analyze the effects of age, education level, number of family members, field productivity, location, and production cost to the total area of paddy field sold. This study used quantitative descriptive method. This research found that age, education level, number of family members, and location of the land had positive relation to the total area of paddy field sold. On the other hand, production cost and field productivity had negative relation to the total area of paddy field sold. Partially, field production and number of family members had no significant effect to the total area of paddy field sold.